Temperature dependence of nitrate-reducing Fe(II) oxidation by Acidovorax strain BoFeN1 – evaluating the role of enzymatic vs. abiotic Fe(II) oxidation by nitrite. Issue 12 (26th November 2021) - Dopffel, Nicole; Jamieson, James; Bryce, Casey; Joshi, Prachi; Mansor, Muammar; Siade, Adam; Prommer, Henning; Kappler, Andreas
ABSTRACT: Fe(II) oxidation coupled to nitrate reduction is a widely observed metabolism. However, to what extent the observed Fe(II) oxidation is driven enzymatically or abiotically by metabolically produced nitrite remains puzzling. To distinguish between biotic and abiotic reactions, we cultivated the mixotrophic nitrate-reducing Fe(II)-oxidizing Acidovorax strain BoFeN1 over a wide range of temperatures and compared it to abiotic Fe(II) oxidation by nitrite at temperatures up to 60°C. The collected experimental data were subsequently analyzed through biogeochemical modeling. At 5°C, BoFeN1 cultures consumed acetate and reduced nitrate but did not significantly oxidize Fe(II). Abiotic Fe(II) oxidation by nitrite at different temperatures showed an Arrhenius-type behavior with an activation energy of 80±7 kJ/mol. Above 40°C, the kinetics of Fe(II) oxidation were abiotically driven, whereas at 30°C, where BoFeN1 can actively metabolize, the model-based interpretation strongly suggested that an enzymatic pathway was responsible for a large fraction (ca. 62%) of the oxidation. This result was reproduced even when no additional carbon source was present. Our results show that at below 30°C, i.e. at temperatures representing most natural environments, biological Fe(II) oxidation was largely responsible for overall Fe(II) oxidation, while abiotic Fe(II) oxidation by nitrite played a less important role. Abstract : This study investigates chemical and microbially catalyzed Fe(II) oxidation across a range of temperatures to develop a quantitative description of enzymatic Fe(II) oxidation coupled to nitrate reduction within the environment.